2017
DOI: 10.1016/j.jcv.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus detection in bulk stool and rectal swab specimens in children with acute gastroenteritis in Norway

Abstract: Both EIA and semi-nested RT-PCR showed a high accuracy, and rectal swab specimens are appropriate for rotavirus diagnosis and may be used as an alternate specimen type when collection of bulk stool is not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have shown that faecal samples and rectal swabs show satisfactory concordance when studying the gut microbiota in adults 6,7 . In the paediatric population, rectal swabs have been compared to faecal samples with respect to the detection of specific pathogens, such as norovirus 8 , but not yet on their performance in analysing the overall microbiota composition. The infant gut microbiota is very dynamic in the first weeks of life 9,10 , so it would be valuable to verify whether rectal swabs give a reliable representation of its composition in this period.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that faecal samples and rectal swabs show satisfactory concordance when studying the gut microbiota in adults 6,7 . In the paediatric population, rectal swabs have been compared to faecal samples with respect to the detection of specific pathogens, such as norovirus 8 , but not yet on their performance in analysing the overall microbiota composition. The infant gut microbiota is very dynamic in the first weeks of life 9,10 , so it would be valuable to verify whether rectal swabs give a reliable representation of its composition in this period.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that rectal swabs are suitable and can be used for the detection of rotavirus when bulk stool is difficult to acquire and that the EIA method has the same high sensitivity of 95% for detection of RV strains compared to the molecular method making it suitable for screening. 20 The present study investigated the appropriateness of rectal swabs for genotyping compared to bulk stool and the correlation was high. These findings support the use of rectal swabs as a convenient and easily accessible specimen type in a rotavirus surveillance program for follow-up on the effects of a vaccine introduction.…”
Section: Some Other European Countries Such As the United Kingdom Andmentioning
confidence: 91%
“…A stool sample from the child was obtained. If a stool sample was not attainable, an anal skin swab was done [26]. When symptoms or medical history could indicate a bacterial infection, samples were also sent for bacterial culture.…”
Section: Study Design Setting and Data Collectionmentioning
confidence: 99%